Challenges and Practices of Implementing Inclusive Education: A Review of Teachers' Classrooms Preparation and Parental Support - Chandra Acharja, Dijendra; Begum, Shamima (South Asian Journal of Social Sciences and Humanities, 2025)
In Bangladesh, inclusive education is underscored in the Constitution, the National Education  Policy 2010, and the SDGs; however, in practice, this is not without challenges. There are not  enough trained teachers; classes are too large, and resources are too scarce. Attitudes towards  linguistic disabilities and marginal communities remain negative; weak school leadership and  teacher reluctance all conspire against their success. Parent engagement is still minimal  because of poverty, stigma, and ignorance. Interference in policy making, as well as  politicization, exacerbates the policy–practice gap. This study examines the reasons behind  the failure of inclusive education in Bangladesh, with a particular emphasis on the classroom  experiences of teachers and the level of parental involvement in the learning process. This  research further argues that to achieve inclusion, the cooperative relationship between parents  and teachers should be strengthened, teachers' competence should be enhanced, classroom  practices should be applied consistently, and long-term plans should be made for  marginalized children.
Keywords: Inclusive Education; Marginalized Community; Prenatal Involvement; Education Leadership